Drug-coated balloon used to treat in-stent restenosis of the renal artery - Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; Moura, Regina [UNESP]; Bertanha, Matheus [UNESP]; Pimenta, Rafael Elias Fares [UNESP]; Yoshida, Ricardo de Alvarenga [UNESP]; Mariúba, Jamil Victor de Oliveira [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2018)
During recent years, drug-coated balloons (DCBs) have emerged as a promising therapeutic option. DCBs directly transfer antiproliferative drugs to the arterial wall in order to decrease myointimal hyperplasia. We describe a case of de novo renal artery in-stent restenosis (ISR) treated with drug-coated balloon angioplasty with acceptable short-term results, achieving blood pressure control using fewer antihypertensive agents. The experience and results obtained with DCBs in other territories could suggest and justify use of this technology in renal artery ISR.
Tratamento da recidiva de reestenose intra-stent renal por angioplastia com balão farmacológico
Keywords: In-stent restenosis; Renal artery stenosis; Renovascular hypertension